Insights into deregulated TNF and IL-10 production in malaria: implications for understanding severe malarial anaemia - Boeuf Philippe S; Loizon Séverine; Awandare Gordon A; Tetteh John KA; Addae Michael M; Adjei George O; Goka Bamenla; AL Kurtzhals Jørgen; Puijalon Odile; Hviid Lars; Akanmori Bartholomew D; Behr Charlotte (Malaria Journal, 2012)
Abstract Background Severe malarial anaemia (SMA) is a major life-threatening complication of paediatric malaria. Protracted production of pro-inflammatory cytokines promoting erythrophagocytosis and depressing erythropoiesis is thought to play an important role in SMA, which is characterized by a high TNF/IL-10 ratio. Whether this TNF/IL-10 imbalance results from an intrinsic incapacity of SMA patients to produce IL-10 or from an IL-10 unresponsiveness to infection is unknown. Monocytes and T cells are recognized as the main sources of TNF and IL-10 in vivo , but little is known about the activation status of those cells in SMA patients. Methods The IL-10 and TNF production capacity and the activation phenotype of monocytes and T cells were compared in samples collected from 332 Ghanaian children with non-overlapping SMA (n = 108), cerebral malaria (CM) (n = 144) or uncomplicated malaria (UM) (n = 80) syndromes. Activation status of monocytes and T cells was ascertained by measuring HLA-DR + and/or CD69 + surface expression by flow cytometry. The TNF and IL-10 production was assessed in a whole-blood assay after or not stimulation with lipopolysaccharide (LPS) or phytohaemaglutinin (PHA) used as surrogate of unspecific monocyte and T cell stimulant. The number of circulating pigmented monocytes was also determined. Results Monocytes and T cells from SMA and CM patients showed similar activation profiles with a comparable decreased HLA-DR expression on monocytes and increased frequency of CD69 + and HLA-DR + T cells. In contrast, the acute-phase IL-10 production was markedly decreased in SMA compared to CM ( P = .003) and UM ( P = .004). Although in SMA the IL-10 response to LPS-stimulation was larger in amplitude than in CM ( P = .0082), the absolute levels of IL-10 reached were lower ( P = .013). Both the amplitude and levels of TNF produced in response to LPS-stimulation were larger in SMA than CM ( P = .019). In response to PHA-stimulation, absolute levels of IL-10 produced in SMA were lower than in CM ( P = ...